Flexible and expeditious assay for quantitative monitoring of alpha-amylase and amyloglucosidase activities - Oliveira, Hugo M. (MethodsX, 2019)
The monitoring of the activity of alpha-amylase and amyloglucosidase is an important tool for studying their role in the hydrolysis of starch. Here we introduced an improved method capable to measure the activity of alpha-amylase and amyloglucosidase from different sources based on a quantitative starch-iodine assay. The developments of the assay sought the consistent preparation of the reagents, the rescale of the assay and the adjustment of the sensitivity. This was complemented by a glucose yield assay for amyloglucosidase that allowed a secondary source of information when insoluble starches were studied. The proposed method showed high precision in long-term use (RSD < 6.3%). Furthermore, all experimental conditions can be adapted according to the equipment available at each laboratory, transforming this method in a broadband analytical tool for screening alpha-amylase and amyloglucosidase activities. • Tailorable assay based on the starch-iodine staining for the determination of alpha-amylase and amyloglucosidase activities. • Enhanced consistence of reagent preparation. • High intra-day and inter-day reproducibility.